Functionality and design influence on fitness fashion - Ong, Derek Lai Teik *; Yang, JoAnne * (2017)
The growing debate between design and functionality dominates within the sportswear industry. Consumers purchase sportswear indirectly due to personal and social intrinsic attributes. Sportswear should be functional, comfortable and safe, developed in line with the performance needs of a person. Hence this study aims to explore the intrinsic factors of consumers purchase intention towards fitness fashion. The conceptual model which is an integration of Social Cognition and Enclothed Cognition theories was analysed using double mediation and reveals that personal and social factors affect perceived importance on functionality and design. While most research claims extrinsic values as main factors of purchase, other perceptions of consumers could come into play which would be beneficial for sportswear brands to identify with and leverage on. The results of this research can assist companies to gain prominence, leveraging on the growing popularity of active lifestyles by designing clothing that match those perceptions.